Study on sustainable agriculture and dimension of needs: a case study patchouli farming in Aceh Jaya. Issue 1 (February 2021) - Zikri, I; Agussabti,; Indra,; Kamaruzzaman, S; Susanti, E; Mujiburrahmad,
Abstract: Aceh patchouli is a global market-leading commodity that has a high economic value regarding the most superior quality characteristics compared to other varieties. However, this condition has not been able to make a real contribution to regional economic growth and to overcome poverty problems in Aceh. This study aims to examine the dimensions of sustainable patchouli farming and its implications for poverty alleviation. This study employed a descriptive explorative method by a case study approach, which focuses on patchouli farmers who engage in a small-scale plantation business in Aceh Jaya, Aceh Province by field observation, in-depth interviews focused group discussions. This study found that the economic condition of the community has stagnated to grow well, even though the performance of patchouli productivity is relatively good. Several crucial issues in patchouli farming practices show a pattern that illustrates the weak support for strengthening the community's economy. This study emphasizes the urgency of strengthening the supporting elements of the integrated Aceh patchouli upstream-downstream business. Therefore, the goal is increasing welfare and growth must be based on changes in behavior to enhance productivity and value chain through the development and strengthening of an innovation system.